Carbamazepine Rash and Prednisone - J Gordon Millichap (Pediatric Neurology Briefs)
The use of prednisone in the treatment of carbamazepine-induced rash in 20 patients is reported from the Divisions of Neurology and Allergy and Immunology, Danbury Hospital, Danbury, CT.